Highly Nitridated Graphene–Li2S Cathodes with Stable Modulated Cycles. Issue 23 (21st September 2015) - Qiu, Yongcai; Rong, Genlan; Yang, Jie; Li, Guizhu; Ma, Shuo; Wang, Xinliang; Pan, Zhenghui; Hou, Yuan; Liu, Meinan; Ye, Fangmin; Li, Wanfei; Seh, Zhi Wei; et al.
Abstract : Ultralong cycle‐life and stable Li2 S‐C/Li cells can be achieved by using highly nitridated graphene and controlling both recharge capacity and voltage.